BS ISO 22863-11. Fireworks. Test methods for determination of specific chemical substances. Part 11. Phosphorus content by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) (14th January 2021) - British Standards Institution,
No abstract available